Does IFRS Help Us Communicate Better? Redifinisi Kualitas Informasi Akuntanis Dalam Perspektif Strategik Pelaporan Keuangan - Utpala Rani; Supanji Setyawan (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
Financial reporting should not only provide benefits to external stakeholders, but it should also provide benefits to the company's susrvival efforts. Therefore, this study elaborates a strategic perspective to define the quality of accounting information. By adopting the concept of qualitative characteristics of IASB and resource-based financial statements, this study provides a theoretical framework for the development of advanced studies on the strategic role of accounting reporting